Prioritizing technical requirements in QFD by integrating grey relational analysis method and analytic network process approach. Issue 1 (2nd February 2015) - Mi, Chuanmin; Xia, Weiguo
Abstract : Purpose: – No matter in product design stage or product quality improvement stage, the product technical requirements (PTRs) impacting on product performance are mainly identified and improved to optimize customer needs (CNs) as greatly as possible. The purpose of this paper is to use a new approach to accurately and properly prioritize PTRs in Quality Function Deployment (QFD). Design/methodology/approach: – Considering the relationship between CNs and PTRs in QFD hard to quantitatively measure and lack of adequate information, the grey relational analysis (GRA) is applied. Besides, owing to the inherent inner dependencies of CNs as well as QFD, the analytic network process (ANP) which is an effective tool to take into account the inner dependencies with network is utilized. Finally, an integrated framework based on GRA method and ANP approach is proposed to determine the importance degrees of PTRs in designing a product. Findings: – The calculation results of the application show that the proposed framework by integrating GRA and ANP is able to determine the importance degrees of PTRs in design a product well. Practical implications: – In the application part the authors can see the proposed framework can be applied to PVC window systems. Owing to that traditional QFD method has been widely used in many fields such as manufacturing industry and service industry, actually the proposed framework has great potential application in the real word. Originality/value: – This paper succeeds in proposing a new framework by integrating GRA and ANP to determine the importance degrees of PTRs in QFD.